Feasibility Study of Interactive Game Technologies to Improve Experience with Inhaler Spacer Devices in Young Children. Issue 2 (December 2016) - Aslam, Tariq; Shakir, Savana; Murray, Clare
Abstract Introduction The correct use of inhaler devices with facemasks and spacers in young children can be difficult for both children and parents, resulting in distress for both, poor adherence and ineffective drug delivery. The aim of this study was to develop and assess the utility and impact of an interactive electronic game designed to improve the experience of spacer devices in young asthmatic children. Methods The Respiratory Aid For Inhaler (RAFIhaler) technology consists of a smartphone mounted on a metered dose inhaler with a valved holding chamber device (spacer) and connected to an electronic sensor adjacent to the outflow valve of the spacer. A custom-designed android application on the smartphone derives the child's breathing patterns from the sensor, translating this information into visible effects on on-screen cartoon characters. After a period of iterative development, the final structure and software design was tested on children at Royal Manchester Children's Hospital who had been admitted with acute wheeze. A survey, including open-ended questions, was administered to assess the parent and child's reaction to the RAFIhaler. Results A total of 14 children (age range 2–7 years; 7 boys) participated in the study and used the RAFIhaler, of whom 13 completed the final survey; all 14 parents completed the survey. All 13 children reported they enjoyed playing the game. Ten of these children (91%) felt that the RAFIhaler helped them in taking their medication, and 13 of the 14 parents felt that RAFIhaler helped their children use their spacer. The one parent who felt that the RAFIhaler was not of any benefit felt his/her child already used the inhaler well. Some of the benefits of the RAFIhaler specifically voiced by parents were "enjoyable" (n = 3), "good distraction" (n = 3), "made child calmer" (n = 2), "helped in breathing/inhalation technique" (n = 3) and "would be useful in home setting" (n = 1). Conclusion Young children may benefit from the incorporation of devices and game applications with use of their inhalers. Feedback from children and parents suggests potential benefits to children may include learning correct use, reducing distress and anxiety and improving overall adherence.